Palisaded myofibroblastoma of lymph node - Sonwane Bharat; Zadke Pandurang; Swami Sunil (Wolters Kluwer Medknow Publications, 2008)
A 60-year female was presented with swelling in the left inguinal region. Microscopically, the left inguinal lymph node shows typical "amianthoid" fibers (hyalinized areas), spindle cell fascicles and hemorrhagic areas in the interstitial spaces with rim of lymphoid tissue. Preoperatively, patient was non-reactive for HIV I and II. This lesion is usually mistaken as neurilemmoma and Kaposi′s sarcoma.